Quality Culture – the Main Value of Academic Community - Pociūtė, Birutė (Acta Paedagogica Vilnensia, 2005)
The purpose of the article was to discover the nature of the quality culture and to present the importance of dissemination of the good practice of quality at the universities. All organizations, the universities as well, have culture in the sense that they are embedded in specific societal cultures and are part of them. Most of the definitions stress the importance of shared norms and values, but other characteristics are equally important: observed behavioural regularities; norms; dominant values; philosophy; rules; organization climate. People are affected by the culture in which they live, but often these values and beliefs are insufficient for helping the individual succeed in the organizations. The individuals need to learn how the organization is functioning. In a second part of the article the problem of quality assurance and quality culture in the lives of universities is described. The main goal of the university is the stimulation of internal quality improvement. But on the other hand, universities meet the difficult question of how to provide public accountability and at the same time to maintain or even increase quality. In the third part of article of Vilnius University in EUA projects „Quality Culture Round I" and „Quality Culture Round JI" is described. The experience was useful in several aspects: participation in the projects reinforced the need to care for quality, to compare the own university with other concrete participating universities and to learn from them. There were a number of initiatives discussed and institutional plans developed, which would be worthy of further consideration by university.
Keywords: higher education; university; quality culture; values; academic community